Tingkat Kematangan Gonad dan Fekunditas Abalon (Haliotis squamata) - Dewa Ayu Angga Pebriani; I Ketut Wija Negara (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2019)
This study aimed to find out the relationship between the maturity level of female abalone gonads with fecundity and egg diameter size of abalone. The results obtained showed that abalone having gonadal maturity level 1 was in the range of 3-4.5cm; gonadal maturity level 2 in the range size of 4.6-6 cm; and gonadal maturity level 3 in the size range> 6 cm. The results of the abalone gonad histology test showed that abalone with gonadal maturity level 1 had more ootid distribution than the primary oocyte. gonadal maturity level 2 has more ootid distribution, primary oocytes than secondary oocytes. Whereas in gonadal maturity level 3 it appears that secondary oocytes dominate which means the gonads are mature and ready to be spawned. The oocyte diameter is getting bigger and more similar simultaneously with an increasing level of gonad maturity. Abalone with gonadal maturity level 1 has an average oocyte diameter of 187 ?m gonadal maturity level 2 of 190 ?m, and gonadal maturity level 3 of 217 ?m.Abalone fecundity for gonadal maturity level 1 ranged from 60,480-86,190 oocytes; TKG 2 ranges from 196,560-214,520 oocyte grains; and TKG 3 ranges from 483,600-518,880 oocyte grains. Based on the results obtained, it can be concluded that the higher the level of maturity of the abalone gonad, the greater the fecundity with the distribution of more secondary oocytes seen in the results of the gonad abalone histology test.